Implementation of the SIPASTI BMD Program in Procurement of Goods and Services at the Sumedang Regency Council Secretariat - Ningrum, Dhesti Widya Nurhasanah; Putri, Elna Berliyana; Annisa, Nur; Hanadila, Novia (Universitas Medan Area, 2023)
This article was written to examine the implementation of the SIPASTI BMD program in the procurement of goods and services at the Sumedang Regency Council Secretariat. The method used in preparing this research report is a descriptive qualitative research method. Data collection techniques use literature studies and field studies. In analyzing data, the following steps are used: data reduction, data presentation, conclusion drawing/verification, and triangulation. Based on the research results, it was concluded that the SIPASTI BMD Program was implemented quite well. However, currently, there are several obstacles in its implementation, including network errors that can delay the input of goods and services and some employees who still don't understand the technology. In overcoming these obstacles, several efforts were made, including waiting for policies from the center and improving the quality of employees with better performance, discipline, and following technical guidance or outreach regarding the program. Suggestions related to this research are to fully encourage the Council Secretariat in determining the policies that will be implemented and pay more attention to employees who do not understand technology who will later be used as support in their work as well as facilitating networks at the Council Secretariat to support the SIPASTI BMD program.